The Effectiveness of Virtual Laboratories in Enhancing Students' Science Process Skills: A Literature Review - Fadillah Deswita Sari; Hayatun Novi Aulia; Lindawati Lindawati; Gunawan Gunawan; Nina Nisrina (Indonesian, 2026)
Virtual laboratories have emerged as a prominent technological intervention in science education. However, a comprehensive synthesis that systematically analyzes their effectiveness across diverse science process skills (SPS) indicators and educational levels remains limited. This study addresses this gap by evaluating the effectiveness of virtual laboratories in enhancing students' SPS through a systematic literature review. Data were compiled from 16 national and international peer-reviewed articles published between 2015 and 2025. The articles were selected based on rigorous inclusion criteria regarding relevance to virtual laboratory interventions and SPS measurements. A qualitative descriptive approach utilizing thematic synthesis was employed to analyze patterns and key findings across the selected literature. The findings demonstrate that virtual laboratories consistently improve various SPS indicators, particularly observing, classifying, predicting, data interpreting, and concluding. Moreover, their efficacy is significantly maximized when integrated with inquiry-based instructional designs, such as guided inquiry and discovery learning. Beyond serving as a practical alternative, virtual laboratories offer critical flexibility, efficiency, and accessibility, functioning as an essential complement to conventional hands-on laboratories in modern science education.